DIABETIC STATUS OF PEOPLE AFFECTED BY LEPROSY IN DONOROJO LEPROSY RECOVERED VILLAGE: A CROSS SECTIONAL STUDY - Nadhila Beladina; Asri Adisasmita (Universitas Ngudi Waluyo, 2021)
Just like diabetes, leprosy also cause painless neuropathic ulcers which process is mediated by Schwann-cell. Biochemical changes on leprosy patients presumed to have role on pathogenesis of diabetes mellitus. This study is aimed to know further about diabetic status on population of people affected by leprosy, as the preliminary study to prove the association between diabetes mellitus and leprosy.Â Data, such as diabetic status, type of leprosy, grade of disability, and other variables are collected from 127 people affected by leprosy in Donorojo leprosy recovered village. Result showed that 19.7% are having diabetes mellitus, and other 23.6% are in pre-diabetic condition. This number is higher than prevalence of diabetes mellitus in Central Java (2.09%) and Indonesia (2%).Â Thus, we recommend further research on this topic and that all leprosy patients should be routinely screened for diabetes mellitus.